2021
DOI: 10.1101/2021.08.12.456173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delta spike P681R mutation enhances SARS-CoV-2 fitness over Alpha variant

Abstract: SARS-CoV-2 Delta variant has rapidly replaced the Alpha variant around the world. The mechanism that drives this global replacement has not been defined. Here we report that Delta spike mutation P681R plays a key role in the Alpha-to-Delta variant replacement. In a replication competition assay, Delta SARS-CoV-2 efficiently outcompeted the Alpha variant in human lung epithelial cells and primary human airway tissues. Delta SARS-CoV-2 bearing the Alpha-spike glycoprotein replicated less efficiently than the wil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 31 publications
7
138
0
Order By: Relevance
“…Finally, enrollment in this study concluded before the arrival of the Delta variant at either study site. It remains unclear how well the effects of vaccination on viral infection dynamics that we describe apply to Delta variant breakthrough infections, given the unique features 12 and enhanced transmissibility 13 of this variant relative to the viruses we captured here.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, enrollment in this study concluded before the arrival of the Delta variant at either study site. It remains unclear how well the effects of vaccination on viral infection dynamics that we describe apply to Delta variant breakthrough infections, given the unique features 12 and enhanced transmissibility 13 of this variant relative to the viruses we captured here.…”
Section: Main Textmentioning
confidence: 99%
“…Finally, enrollment in this study concluded before the arrival of the Delta variant at either study site. It remains unclear how well the effects of vaccination on viral infection dynamics that we describe apply to Delta variant breakthrough infections, given the unique features 12 and enhanced transmissibility 13 of this variant relative to the viruses we captured here. Overall, our data suggest that vaccinated individuals are less likely to be shedding infectious virus at a given viral genome load and shed for a shorter period of time compared to unvaccinated and report fewer days of symptoms.…”
mentioning
confidence: 99%
“…SARS-CoV-2 viral loads are significantly higher in both vaccinated and unvaccinated individuals infected by Delta VOC (1). At least in part this appears to be driven by increased infectivity due to the furin cleavage enhancing P681R mutation (2). Other potential mechanisms have been proposed, including reduced immune recognition resulting from diminished neutralizing antibody binding to spike protein epitopes, particularly in the receptor binding domain (RBD) of the spike protein (3).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the variants carrying spike L452R change are likely to be more transmissible and infective and less susceptible to the neutralizing antibodies from convalescent patients and vaccine recipients (Deng et al, 2021). The variant bearing P681R, such as B.1.617.2, has an increased furin-mediated cleavage at the S1/S2 cleavage site that would lead to enhanced viral fusogenicity and exhibit a higher pathogenicity (Liu et al, 2021b;Peacock et al, 2021;Saito et al, 2021). It was also observed that in the hamster model, B.1.617.1 has a higher pathogenicity than has B.1 (Yadav et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%